The Influence of Religious Coping on Academic Stress in Students of The Faculty of Medicine, Bandung Islamic University - Maulana Abdul Malik Ibrahim; Khasanah, Andhita Nurul (UNISBA Press, 2024)
Abstract. Academic stress is a stimulus caused by academic stressors and how they react physically, emotionally, behaviorally and cognitively to these stressors (Gadzella & Masten, 2005). Religious coping is coping with stress with religious patterns and methods such as prayer and worship with the aim of eliminating stress (Pargament 1999). The aim of this research is to determine the effect of religious coping on academic stress in students at the Faculty of Medicine, Islamic University of Bandung. The subjects in this study were medical students N = 245 people. The analysis technique used is simple linear regression. The tool for measuring religious coping uses the Iranian Coping Religious Scale by Alfakseir & Coleman (2011) which has been adapted by Shabrina (2017). Meanwhile, the academic stress measuring tool uses the Student Life Stress Inventory by Gadzella & Masten (2005) which has been adapted by Praghlopati et al. (2021). The research results showed that there was a negative influence of 48.7% on academic stress in students at the Faculty of Medicine, Islamic University of Bandung. Abstrak. Stres akademik merupakan suatau stimulus yang disebabkan oleh stressor akademik dan bagaimana reaksi mereka terhadap fisik, emosi, perilaku dan kognitif terhadap stressor tersebut (Gadzella & Masten, 2005). Coping religius merupakan coping stress dengan pola dan meted religius seperti berdoa, beribadah dengan tujuan menghilangkan stress (Pargament1999). Tujuan dari penelitian ini adalah untuk mengetahui pengaruh coping religius terhadap stress akademik pada mahasiswa Fakultas Kedokteran Universitas Islam Bandung. Subjek pada penelitian ini adalah mahasiswa kedokteran N = 245 orang. Teknik analisis yang digunakan regresi linear sederhana. Alat ukur coping religius menggunakan Iranian Coping Relgius Scale oleh Alfakseir & Coleman (2011) yang sudah di adaptasi oleh Shabrina (2017). Sedangkan alat ukur stress akademik menggunakan Student Life Stress Inventory oleh Gadzella & Masten (2005) yang sudah di adaptasi oleh Praghlopati et al. (2021). Hasil penelitian menunjukkan bahwa ada pengaruh negatif sebesar 48.7% terhadap stress akademik pada mahasiwa Fakultas Kedokteran Universitas Islam Bandung.